Investigating the relationship between motivation, competence, and commitment: A mediation model of self-efficacy on employee performance in the hospitality industry - Sahabuddin, Romansyah; Haeruddin, Ikhwan Maulana; Burhanuddin, Burhanuddin (Edelweiss Applied Science and Technology, 2025)
This study delves into the multifaceted relationships among motivation, competence, and commitment as foundational determinants of employee performance in the hospitality sector, emphasizing the transformative role of self-efficacy as an intervening variable that reinforces these linkages. Leveraging a robust quantitative, survey-based methodology, data were meticulously collected through a rigorously validated questionnaire administered to a purposively selected cohort of hotel employees. The sample design employed purposive sampling, and advanced path analysis techniques were utilized to disentangle both direct and mediated effects of the independent variables on performance outcomes. Empirical findings substantiate that motivation, competence, and commitment exert a significant and positive influence on employee performance, with self-efficacy emerging as a pivotal mediating construct that enhances these interrelations. This research underscores the strategic imperative of embedding self-efficacy within human resource management paradigms as a cornerstone for optimizing workforce efficacy. In the context of the increasingly competitive and service-driven hospitality industry, the findings advocate for a paradigm shift toward the strategic cultivation of self-efficacy to drive organizational productivity, competitive differentiation, and sustainable growth. By addressing critical gaps, this study enriches the discourse on performance management, providing a holistic and integrative framework that aligns theoretical insights with pragmatic applications.